Cardiovascular effect of varying interval training frequency in rehabilitation of severely burned children - Tapking, Christian (Journal of burn care & research, 2019)
Abstract. Structured exercise programs initiated after acute hospitalization can improve muscle strength and mass, cardiorespiratory capacity, and quality of l